(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The structural and value developments resulting from the cultural revolution in contemporary societies, parallel to the growth, have sought attention to the category of memory. Cultural memory has become an important tool in producing discourses and representations, as well as forming the cultural identity of social groups and communication with many institutions and social structures. The present article seeks to describe the contexts, functions, and effects of memory studies as an interdisciplinary academic tradition and introduce its main approaches and methods, especially in the tradition of cultural studies. For this purpose, the approach of neuro-aesthetics was utilized, and the Atonement Novel was reviewed, which in addition to adding important agendas in the study of everyday life and popular culture, also has a great contribution to the connection of humanities and social sciences and a better understanding of cultural and social complexities. Given the results, the major probable addition for the humanities from discussions with neuroscience is a pulling together of consideration on a few center inquiries of normal interest.